2019
DOI: 10.25134/ieflj.v5i2.1835
|View full text |Cite
|
Sign up to set email alerts
|

Using Orai Application in Teaching Pronunciation

Abstract: Teaching in 4.0 era cannot be separated with Information and Communication Technology (ICT). There are many applications that can be used in learning and teaching process. ORAI application is chosen to be used as teaching tool in learning pronunciation. The main objective of this research is to discover the pro and cons from students as the main user in using ORAI application in learning pronunciation. This research implemented qualitative as research method and the participants of the research was 35 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Willis (2021) [15] conducted a study on the impact of online task-based learning in language education, resulting in significant discoveries and notable effects. Firstly, it has been shown that learners who engage in task-based learning using online platforms have higher levels of language competence in comparison to their peers in conventional instructional environments [16,17]. Second, online tasks allow students to learn about different cultures, which helps them become more interculturally competent.…”
Section: Online Task-based Learningmentioning
confidence: 99%
“…Willis (2021) [15] conducted a study on the impact of online task-based learning in language education, resulting in significant discoveries and notable effects. Firstly, it has been shown that learners who engage in task-based learning using online platforms have higher levels of language competence in comparison to their peers in conventional instructional environments [16,17]. Second, online tasks allow students to learn about different cultures, which helps them become more interculturally competent.…”
Section: Online Task-based Learningmentioning
confidence: 99%
“…Before you may study the following lesson's topic, you must finish the first three steps of that content. An app called Orai was created to assist students in becoming better English speakers (Suryani et al, 2019).…”
Section: Oraimentioning
confidence: 99%
“…Each content consists of three content stages that must be completed before you can learn the next lesson content. Orai is an application purposed to help students to be better English speakers (Suryani et al, 2019).…”
Section: Oraimentioning
confidence: 99%